Naming the enemy : anti-corporate movements confront globalization - Starr, Amory, 1968- (London : Pluto Press Australia, 2000)
'Naming the Enemy is the first systematic documentation of this international resistance to transnational corporations and globalization that has so recently burst into the public gaze with the street protests in Seattle, Washington, London and Prague. This book is relevant to activists as well as students and scholars of globalization, new social movements and political economy.'--BOOK JACKET
Includes bibliographical references (p. [239]-253) and index
Keywords: International business enterprises; International relations; Social movements; Social change